2019
DOI: 10.1097/md.0000000000015284
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D3 on blood pressure in people with vitamin D deficiency

Abstract: Objective: To evaluate the effect of vitamin D 3 on blood pressure in people with vitamin D deficiency. Methods: Randomized controlled trials (RCTs) were electronically searched databases including CNKI, VIP, WanFang Data, the Cochrane Library, PubMed, and EMbase which were about oral vitamin D 3 among people with vitamin D deficiency from inception to December 2017. Two reviewers independently screened literature ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 23 publications
(15 reference statements)
7
25
0
3
Order By: Relevance
“…Patients with deficiency in vitamin D may acquire the effects of vitamin D supplementation 20 . However, administering vitamin D to participants who meet the same criteria can give zero results with regard to a decrease in BP because of the shorter time of administration (only 8 weeks with almost the same dose) 25 .In addition, an updated meta-analysis’s results were similar to our study in that subgroup analysis showed vitamin D supplementation may reduce SBP and DBP in patients with low 25(OH)D concentrations and hypertension 5 .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Patients with deficiency in vitamin D may acquire the effects of vitamin D supplementation 20 . However, administering vitamin D to participants who meet the same criteria can give zero results with regard to a decrease in BP because of the shorter time of administration (only 8 weeks with almost the same dose) 25 .In addition, an updated meta-analysis’s results were similar to our study in that subgroup analysis showed vitamin D supplementation may reduce SBP and DBP in patients with low 25(OH)D concentrations and hypertension 5 .…”
Section: Discussionsupporting
confidence: 68%
“…The other important finding in our study was significant differences in SBP and DBP changes among the hypertensive subgroup. Previous meta-analyses have also revealed a significant effect of vitamin D on BP in patients with hypertension at the baseline and no significant decrease in normotensive patients at the baseline 5 , 36 . In contrast to our findings, a meta-analysis by Golzarand et al .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A large meta-analysis of 81 studies by Mirhosseini et al [64] reported that vitamin D improved blood pressure, dyslipidemia, and hypertension. A recent meta-analysis on 17 RCTs reported that vitamin D supplementation reduced systolic and diastolic pressures in vitamin D deficient and in hypertensive individuals [65]. In contrast, Golzarand et al [66] reported no effect of vitamin D supplementation on blood pressure.…”
Section: Discussionmentioning
confidence: 99%